Regional Products With the Protection of Origin in Serbia Tourism Offer - Miloš Ćirić; Bojana Kalenjuk; Ivana Janković (Indonesian Journal of Tourism and Leisure, 2020)
The product protection system has been created in order to keeping up with the development of tourism and the need to offer and highlight unique agricultural, food, and gastronomic products.  In this way, trademarks have positive effects on users of services or products, creating a clear picture of specific, authentic characteristics of food and beverages. Their constant production and sales have a positive impact on the economic development of the country - the region from which the products come. The paper has the task to showcase protected products by regions that can favorably affect the economic growth through sales and supply within catering and tourism facilities. This paper aims to consider the number, types, and characteristics of these products within the region, as important part of the gastronomic offer, tourist and economic development of the country. The research was conducted on the basis of appropriate documentation of data available to the Institute for the Intellectual Property of the Serbia. Based on the conducted research, it was concluded that in the territory of the Serbia, the region with the largest number of protected products is Vojvodina, while Šumadija is the region with the smallest number of protected products.